2013
DOI: 10.4081/ijas.2013.e76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Faba BeanVicia FabaVar.Minor) Inclusion in Starter and Growing Diet on Performance, Carcass and Meat Characteristics of Organic Slow-Growing Chickens

Abstract: This paper assesses the effect of faba bean (Vicia Faba minor), in partial substitution of soybean, on productive performance, carcass and meat traits of slow-growing chickens readed under the organic method. Faba bean was used in both starter (1-21 d) and growing/finisher diets (22-120 d). One thousand birds were fed two different diets containing respectively, soybean or faba bean as the main protein source for the entire rearing period. The birds of each group were slaughtered at 120 d of age. The productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
8
27
2
Order By: Relevance
“…A significantly lower percentage of skin with subcutaneous fat (P < 0.01) and abdominal fat (P < 0.05) found in this study in the carcasses of chickens provided with mixtures containing high-tannin faba bean was a reversal of the results obtained by Usayran et al [2014]. Laudadio et al [2011], Osek et al [2013] and Dal Bosco et al [2013] reported no significant effect of diets with faba bean on the percentage of abdominal fat in carcasses of chickens, while Shargh and Azari [2010] found its lowest percentage in chickens fed a mixture with the highest (18%) content of faba bean.…”
Section: Resultscontrasting
confidence: 50%
See 3 more Smart Citations
“…A significantly lower percentage of skin with subcutaneous fat (P < 0.01) and abdominal fat (P < 0.05) found in this study in the carcasses of chickens provided with mixtures containing high-tannin faba bean was a reversal of the results obtained by Usayran et al [2014]. Laudadio et al [2011], Osek et al [2013] and Dal Bosco et al [2013] reported no significant effect of diets with faba bean on the percentage of abdominal fat in carcasses of chickens, while Shargh and Azari [2010] found its lowest percentage in chickens fed a mixture with the highest (18%) content of faba bean.…”
Section: Resultscontrasting
confidence: 50%
“…For no effect of faba bean (variety percentage) was shown on carcass quality and slightly better musculature was observed, as well as significantly lower fatness of chickens. Many other authors [Moschini et al 2005, Nale et al 2010, Shargh and Azari 2010, Laudadio et al 2011, Osek et al 2013, Dal Bosco et al 2013, by introducing 16, 25, 31 or 50% faba bean into the diet of chickens, did not observed a significant impact of this feed on carcass quality and the percentage of breast and thigh muscles. Diaz et al [2006] showed a significant increase in the percentage of breast muscles in carcasses of chickens fed mixtures with faba bean compared to controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is extremely important from the point of view of the consumer for a broiler chicken meat has a high content of easily digestible protein and the standard value and the low energy value associated with the small amount of fat [Grześkowiak et al 2011, Kunachowicz et al 2014]. Among the above-mentioned components of muscle protein content remained relatively constant, while the amount of intramuscular fat and its fatty acid profile are much more variable depending on a number of factors, including the feeding [Meluzzi et al 2009, Dal Bosco et al 2013, Osek et al 2013, Pietrzak et al 2013, Usayran et al 2014, Biegniewska et al 2016. Any change in the composition of the ration chickens can affect the fatty acid profile of the meat.…”
Section: Introductionmentioning
confidence: 99%